Weaving critical hope: story making with artists and children through troubled times. (19th January 2022) - Stephenson, Lisa; Daniel, Alastair; Storey, Vicky
Abstract: Re‐imagining Home was a collective immersive story response for children ages 7–12 years during Covid curated by artists from The Story Makers Company. This experience focused on connecting children in new ways through the processes of drama and storying. This paper explores the nuanced responses that children and artists negotiated online/offline story spaces as they lived through these experiences. ARTography (Irwin, 2013) is used as a form of practitioner inquiry from three of the eight artists perspectives, to critically examine the tensions of embedding our affective offline practices online. This includes exploring the rhizomatic ways in which children engaged both online/offline through the artefacts that they shared. The ways in which these hybrid story spaces reflected our affective experiences are explored as the 'richness of the meanwhile' (Bogost in Facer 2019, p. 7), described as 'the dense network of activity going on at any one time'. These shared 'fragmentary' stories are explored as a critical pedagogy of hope, considering how the Story Weave offered new possibilities for reimagining future educator practices in troubled times.